PENGEMBANGAN DIGITAL MARKETING UNTUK MENINGKATAN KAPASITAS USAHA PADA UMKM TAS ANTING DI DESA PUTUKREJO KALIPARE MALANG - Wafiyatu Maslahah; Adzimatnur Muslihasari; Arif Wahyu Hidayat; Hafit Bastomi; Agus Afrizal; Antono, Antono; Alvin Nanda Rifky (Bajang Institute, 2024)
One of the problems faced by the UMKM Tas Anting in Putukrejo Village is the problem of marketing and skills in using technology. UMKM Tas Anting in Putukrejo Village require technology-based business development so that they can compete with new businesses that are online. Online marketing is suitable for businesses that are just starting out. Certainly cost-effective, because you don't have to hold a place or shop to display products, you can control yourself without having to recruit employees, unlimited working time or hours, and have a wide market reach, because online marketing is usually supported by a website or social media (Facebook, Instagram, WA, etc.) This strategy is to prove the influence of digital marketing on the sales performance of the UMKM Tas Anting product in Putukrejo Village which was developed by the KKN-T 06 Group at the Islamic University of Raden Rahmat Malang